Label accuracy of unregulated cannabidiol (CBD) products: measured concentration vs. label claim - Erin Johnson; Michael Kilgore; Shanna Babalonis (BMC, 2022)
Abstract Background The legalization of hemp in the USA has led to tremendous growth in the availability of hemp-derived products, particularly cannabidiol (CBD) products. The lack of regulatory oversight in this industry has resulted in the marketing and sale of CBD products with questionable ingredients and quality. The aim of the current study was to examine the CBD content in 80 commercially available hemp-derived CBD products purchased from online and local retailers. Epidiolex® was also included in the study as a positive control. Methods Hemp-derived CBD products were selected to represent products readily available to residents of Central Kentucky. The samples were comprised of local and national brands produced in a variety of locations inside and outside of Kentucky. The products were analyzed by liquid chromatography-tandem mass spectrometry (LC-MS/MS), and the analytical findings were compared to the label claims for CBD content. Descriptive statistics and normal-based confidence intervals were calculated using Microsoft Excel. Results The label claims for CBD content ranged from 7.5 to 60 mg/mL, while LC-MS/MS analysis detected a range of 2.9 to 61.3 mg/mL. Of the 80 products evaluated, 37 contained CBD concentrations that were at least ± 10% different than the concentration listed on the label (range of 0.9 to 30.6 mg/mL from label claim) - 12 products contained < 90%, while 25 products contained > 110%. The degree of concordance for the samples tested using ± 10% tolerance from label claim was 54%. Conclusions These data suggest that additional regulation is required to ensure label accuracy as nearly half of the products in this study were not properly labelled (i.e., not within a ± 10% margin of error). Consumers and practitioners should remain cautious of unregulated and often-mislabeled CBD products due to the risks of taking too much CBD (e.g., drug-drug interactions, liver enzyme elevations, increased side effects) and the consequences of taking too little (e.g., no clinical benefits due to underdosing). The results of this study support the continued need for good manufacturing practices and testing standards for CBD products.